Alpha-fetoprotein production by a hepatoid adenocarcinoma of the uterus. Issue 5 (May 1996) - Yamamoto, R; Ishikura, H; Azuma, M; Hareyama, H; Makinoda, S; Koyama, Y; Nishi, S; Fujimoto, S
Abstract : A case of a 62 year old Japanese woman with an endometrial adenocarcinoma producing alpha-fetoprotein (AFP) is described. Microscopically, the tumour was composed of a major medullary portion and a minor tubular adenocarcinoma which had invaded the myometrium, the myometrial lymphatics and blood vessels. Neoplastic cells in the medullary portion were polygonal with glycogen-rich cytoplasm. Vascular permeation by neoplastic cells was prominent. Extensive hepatoma-like features were observed. The tumour cells lacked features suggestive of a diagnosis of embryonal carcinoma or endodermal sinus tumour. The production of AFP by the tumour cells was demonstrated immunohistochemically using the PAP technique. Only two cases of AFP producing endometrial adenocarcinomas have been reported previously.